PrxBa1-xCoO3 Oxide Electrodes for Oxygen Evolution Reaction in Alkaline Solutions by Chemical Solution Deposition. Issue 3 (1st January 2016) - Bick, D. S.; Griesche, J. D.; Schneller, T.; Staikov, G.; Waser, R.; Valov, I.
Abstract : Perovskite Prx Ba1-x CoO3 (PBCO) thin film electrodes were used in a water splitting electrolysis cell for oxygen evolution reaction (OER) and studied by cyclic voltammetry. We systematically varied the composition of the PBCO deposited by spin-coating using different Ba to Pr ratios. The influence of Pr-content in the perovskite on catalytic OER activity is discussed for two different substrates, namely platinized Si and laser polished Ti. The crystallographic structure of the thin films and the oxidation state of the metal ions in the perovskite is examined by XRD and X-ray photoelectron spectroscopy, respectively. In addition, we propose a laser-polishing process of the Ti substrates as alternative to the classical surface treatment, providing smooth and homogeneous surfaces. Accelerated life time tests have shown the advantage of the catalytically active films deposited on laser polished Ti substrates.